Identification of Platelet Antigens by Immunoprecipitation of Unlabelled Platelet Glycoproteins - Stenziger, Werner; Kehrel, Beate; van de Loo, Jürgen (Thrombosis and Haemostasis, 1990)
A time-saving and sensitive method for the identification of antigens on unlabelled platelet glycoproteins (GP) based on immunoprecipitation has been developed. Platelet solubilisates were incubated with antibodies to form GP-antibody complexes that were precipitated with Protein G Sepharose 4 Fast Flow (PGS). Pcs-bound material was eluted, separated by SDSPAGE under reducing conditions and visualized by silver staining. The method was designed as an alternative to radioimmunoprecipitation for laboratories not equipped to work with radioactive substances. It is proposed as a complementary procedure for the characterization of platelet GP antigens by murine monoclonal antibodies and human alloantibodies.